Impact Analysis and Modification of Front Inner Bumper - Adi Siswanto, Waluyo; Kang Teng, Tan; Md Salleh, Salihatun; ., Binyamin (International Journal of Engineering and Technology, 2019)
This paper presents the modification of an existing front inner bumper of a passenger car.Â The manufactured bumper was captured by using three-dimensional scanner ATOS-GOM in order to obtain the CAD cloud geometrical data. Impact analysis was the conducted by employing dynamic explicit time stepping algorithm software IMPACT. The software was firstly benchmarked with known experimental results of beam under low velocity impact. The simulation and experimental results of the deflected beam were relatively comparable with variation from 1.6 to 9.5%. Two impact simulations were then performed on the real bumper; 40 percent offset collision and full frontal collision. The collisions were tried in different velocity of 48 km/h, 64 km/h and 110 km/h. The results were utilized as the benchmarking platform to enhance the bumper performance. Two alternative design modification were tried. Both design A and B exhibit significant increase of internal energy adsorbed. Even with the increase of energy being adsorbed by both the designs, still design B exhibits superiority in every way possible.Â